PSYCHODIAGNOSTIC APPROACHES FOR EARLY DETECTION AND PREVENTION OF STUTTERING IN CHILDREN - Abdullayeva Karomat Islom qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article explores psychodiagnostic approaches for the early detection and prevention of stuttering in children. The study analyzes how standardized assessments, observational methods, and psychological screening tools can identify risk factors, emotional triggers, and early signs of speech disfluency. Emphasis is placed on integrating psychodiagnostic findings with preventive interventions to support timely and individualized strategies for improving speech fluency. The results indicate that early psychodiagnostic evaluation facilitates effective intervention, reduces the likelihood of persistent stuttering, and promotes emotional and social development in children.